Unveiling the Role of the Integrated Endoplasmic Reticulum Stress Response in Leishmania Infection – Future Perspectives - Dias-Teixeira, K. L.; Pereira, R. M.; Silva, J. S.; Fasel, N.; Aktas, B. H.; Lopes, U. G. (Frontiers in Immunology, 2016)
The Integrated Endoplasmic Reticulum Stress Response (IERSR) is an evolutionarily conserved adaptive mechanism that ensures Endoplasmic Reticulum homeostasis and cellular survival in the presence of stress including nutrient deprivation, hypoxia, and imbalance of Ca+ homeostasis, toxins and microbial infection. Three transmembrane proteins regulate integrated signaling pathways that comprise the IERSR, namely, IRE-1 that activates XBP-1, the pancreatic ER kinase (PERK) that phosphorylates the eukaryotic translation initiation factor 2 and Transcription Factor 6 (ATF6). The roles of IRE-1, PERK and ATF4 in viral and some bacterial infections are well characterized. The role of IERSR in infections by intracellular parasites is still poorly understood, although one could anticipate that IERSR may play an important role on the host`s cell response. Recently, our group reported the important aspects of XBP-1 activation in Leishmania amazonensis infection. It is, however, necessary to address the relevance of the other IERSR branches, together with the possible role of IERSR in infections by other Leishmania species, and furthermore to pursue the possible implications in the pathogenesis and control of parasite replication in macrophages.